Transient receptor potential V4 channel stimulation induces reversible epithelial cell permeability in MDCK cell monolayers. Issue 16 (26th June 2019) - Mukaiyama, Minagi; Yamasaki, Yohei; Usui, Takeo; Nagumo, Yoko
Abstract : The transient receptor potential V4 channel (TRPV4) is responsive to a variety of physical and chemical stimuli, including a synthetic agonist GSK1016790A (GSK). Here, we show that TRPV4 is functionally expressed in, and that GSK induces the reversible opening of tight junctions (TJs) in epithelial Madin–Darby canine kidney II monolayers. Stimulation of TRPV4 by GSK induces an increase in fluorescein isothiocyanate‐conjugated dextran (4 kDa) permeability and a reduction in transepithelial resistance, and these responses are blocked by pretreatment with the specific TRPV4 antagonist. Small conductance, but not large conductance Ca 2+ ‐activated K + channels, TRPA1 channel, and cofilin activation are involved in TRPV4‐mediated reversible opening of TJs. These results suggest that a novel mechanism underlies TRPV4‐mediated regulation of the tightness of epithelial barriers. Abstract :